High-resolution geological-tectonic of the Caquerelle Anticline and surrounding geological features in the western boundary of the Delémont Basin area, Jura fold-and-thrust belt (Switzerland) - Matteo Basilici; Jon Mosar; Sandra Borderie; Christophe Nussbaum (Journal of Maps)
The Caquerelle Anticline is situated within the Internal Jura (Switzerland). Here, inherited basement faults developed during Paleogene have influenced the deformation of the detached Mesozoic and Cenozoic sedimentary cover, likely contributing to the formation of the Delémont Basin. The Caquerelle Anticline has thus become a key area for understanding the geodynamics of the basin. In this work, we combined (i) pre-published geological maps and numerous journal publications, (ii) fieldwork integrating classical field methodologies and drone surveys, and (iii) meticulous digital mapping of the digital elevation model 'swissALTI3D', to create a 1:25,000 high-resolution geological-tectonic map of the Caquerelle Anticline and surrounding geological features. According to our interpretation, the Caquerelle Anticline divides two areas with different shortening directions. This phenomenon is attributed to at least one east-dipping basement fault located in the study area. This fault influenced the following compressive deformation of the overlying sedimentary cover, into a transpressive setting.